Análisis de la demanda de vivienda y su relación con el ingreso familiar de los habitantes de la provincia de chimborazo cantón riobamba durante el año 2014. - Buñay Gavidia, Cristian Javier (2016)
This research consists of chapters. Chapter I in which the problem is formulated to investigate, based on the general and specific objectives to achieve as the research purposes. Revealing the rationale and importance of this study. Chapter II deals with the development of framework, revealing the history and definitions needed to develop this research by analyzing the determinants of housing demand as they are developed local such as: demographic, economic, legal and financial factors, in both levels national and local. In addition, econometric models relating to the housing sector are mentioned. Additionally, this chapter raises the hypothesis, and the variables of this research are identified. In Chapter III, the methodological framework in which the methodology and the type of research is determined and explained. Similarly, the population and sample will help to implement surveys set, which will be analyzed and interpreted according to the results. In addition, the hypothesis by applying the econometric model is checked. In Chapter IV the conclusions are drawn once the investigation is finished and recommendations assist in the solution of the posed problem.